Da (in)constitucionalidade das súmulas e precedentes vinculantes em detrimento do convencimento motivado do Juíz e das cláusulas pétreas : limites e possibilidades para uma mudança hermenêutica à luz da teoria da decisão - Araújo, Jenaldo Alves de (2023)
Constitutional Amendment no. December 45, 2004, together with Law n.11.417, of December 2006, introduced the binding summary into Brazilian Law, making the decisions of the Federal Supreme Court become mandatory for the other courts of the Judiciary, as well as for Direct and Indirect Public Administration. This institute caused several discussions in the legal world, causing constitutionalists and proceduralists to raise countless questions and positions on the matter, mainly with regard to the application of the aforementioned institution in relation to jurisdictional activity, since the aforementioned summary is an affront, mainly fundamental, social rights and the fundamental principles of the national system, in particular, the Principle of Convincing the Judge. As a result, such questions unfolded in such a way that they also brought into their framework accentuated positions relating to the principles of double degree of jurisdiction, due legal process, among others, which are constitutional principles expressed as part of the fundamental rights provided for in the Federal Constitution. It is exactly in light of this great offense that the present study is proposed, focused on the confrontation between the institute created in 2004, the binding summary, and the Principle of the Judge's motivated Convincing. The adoption of such a measure aims to “unburden” the Judiciary Branch tied to an alarming number of processes and put an end to the existing slowness. On the other hand, the implementation of the precedent with binding effect could cause the Judiciary to become rigid, as by forcing judges to follow this procedure in a mechanical and alienated manner, prohibiting a basic principle of law, namely: the motivated conviction of the judge to say the law in the specific case.